2014
DOI: 10.1371/journal.pone.0098867
|View full text |Cite
|
Sign up to set email alerts
|

Increased Growth-Inhibitory and Cytotoxic Activity of Arsenic Trioxide in Head and Neck Carcinoma Cells with Functional p53 Deficiency and Resistance to EGFR Blockade

Abstract: Background and PurposeMutations in the p53 gene are frequently observed in squamous cell carcinoma of the head and neck region (SCCHN) and have been associated with drug resistance. The potential of arsenic trioxide (ATO) for treatment of p53-deficient tumor cells and those with acquired resistance to cisplatin and cetuximab was determined.Material and MethodsIn a panel of 10 SCCHN cell lines expressing either wildtype p53, mutated p53 or which lacked p53 by deletion the interference of p53 deficiency with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
3
3
0
Order By: Relevance
“…Different point mutations in TP53 binding sites activate paradoxical cellular programs such as cell death by apoptosis or DNA damage response mechanisms 17,18 . Besides, additional experiments using non-malignant cells are essential to assess whether a combination of ATO with radiation therapy has a selective effect in cancer cells, a study in head and neck carcinoma corroborates with our findings 19 . The authors showed that the combination of ATO with irradiation was shown able to reduce colony formation in p53-deficient cells, which was associated with DNA damage, G2/M arrest, and apoptosis 19 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Different point mutations in TP53 binding sites activate paradoxical cellular programs such as cell death by apoptosis or DNA damage response mechanisms 17,18 . Besides, additional experiments using non-malignant cells are essential to assess whether a combination of ATO with radiation therapy has a selective effect in cancer cells, a study in head and neck carcinoma corroborates with our findings 19 . The authors showed that the combination of ATO with irradiation was shown able to reduce colony formation in p53-deficient cells, which was associated with DNA damage, G2/M arrest, and apoptosis 19 .…”
Section: Discussionsupporting
confidence: 88%
“…Besides, additional experiments using non-malignant cells are essential to assess whether a combination of ATO with radiation therapy has a selective effect in cancer cells, a study in head and neck carcinoma corroborates with our findings 19 . The authors showed that the combination of ATO with irradiation was shown able to reduce colony formation in p53-deficient cells, which was associated with DNA damage, G2/M arrest, and apoptosis 19 . Moreover, the treatment (ATO + irradiation) was already explored in one cerebellar HGNET-BCO SHH+/GLI+ tumor, that achieved six-months tumor remission with therapy's proper safety and tolerability 12 .…”
Section: Discussionsupporting
confidence: 88%
“…In line with our findings, recent evidence has shown that ATO can induce apoptosis in a p21-and p53-dependent manner in other tumor models (e.g., hepatocellular carcinoma and glioma) [13,32]. Numerous studies have revealed that ATO can enhance the extrinsic apoptotic pathway by upregulating cell surface death receptors and/or ligands (e.g., Fas and TRAIL), leading to the activation of caspase 8 [33,34]. Furthermore, it has been found that ATO activates the intrinsic apoptotic pathway in different tumor cell lines through mitochondrial membrane disruption, resulting in the release of cytochrome c and the consecutive activation of caspases 3/7 and 9 [35,36].…”
Section: Discussionsupporting
confidence: 91%
“…TP53 and CDKN2A were amongst the most frequently mutated genes in the ORL cell lines (94% and 63% respectively). As the mutation status of these genes can add value by improving our overall understanding of tumor biology and influence on drug response [ 21 , 22 ], we validated a sub-set of these mutated genes by Sanger sequencing. To this end, we sequenced exons 4–11 of the TP53 and exons 1–3 of the CDKN2A genes and essentially validated the mutations identified from RNAseq.…”
Section: Resultsmentioning
confidence: 99%